Comparison of two scales for evaluation of smile and dental attractiveness - Pedro Lima Emmerich Oliveira; Andrea Fonseca Jardim da Motta; Clarice Julia Guerra; José Nelson Mucha (Dental Press Editora, 2015)
OBJECTIVE: To compare the visual analogue scale (VAS) and the simplified Q-sort method used to investigate the highest level of agreement among dentists, orthodontists and laypeople when assessing smile and dental attractiveness. MATERIAL AND METHODS: An album containing 258 photos of 86 individuals with their lips at rest, a slight and broad smile, was assessed by 25 dentists (general clinicians and various specialties), 23 orthodontists and 27 laypeople with regard to smile and dental attractiveness. To this end, both VAS and simplified Q-sort method were used. Agreements were calculated by intraclass correlation coefficient (ICC). RESULTS: For the single measurement between the VAS method and the simplified Q-sort method, all simplified Q-sort rates were higher in all groups. The simplified Q-sort method results ranged between 0.42 and 0.49 while those of the VAS method varied between 0.37 and 0.42. The simplified Q-sort method also presented higher mean measurement values (0.95 and 0.96) in comparison to VAS (0.94 and 0.95). CONCLUSIONS: Both scales may be considered reliable for evaluating smile and dental attractiveness; however, the simplified Q-Sort method presented slightly higher values than the VAS method.